Effectiveness of Blended Learning with Flipped Classroom Method on the Knowledge Level and Self Efficacy among Nurses During the Basic Life Support Course - Fitra Jayadi; M. Rizki Akbar; Aan Nuraeni (Babali Health, 2022)
Introduction: The blended learning with flipped classrooms combination may propose a more effective and efficient way to share information in the course sessions. However, a scientific-based investigation is required to confirm its effect on knowledge and self-efficacy improvement during the BLS course learning sessions. Methods: This was a quasi-experimental study with a pre-post test design, enrolling nurses who were participating in BLS Courses. Participants were assigned into two groups: a control group with Blended learning (BL) or conventional learning approach (n=30) and an experimental group with Blended Learning with Flipped Classroom (BLFC) (n=30). A knowledge questionnaire from the American Heart Association (AHA) Guidelines and a Self-Efficacy questionnaire of Resuscitation Self-Efficacy Scale (RSES) were employed to gather the study data. Data were then analyzed using the SPSS with the mean, median, Wilcoxon, and Mann-Whitney tests. Results: Wilcoxon test revealed a significant mean difference in knowledge and self-efficacy in the BL group with a p-value of 0.000 and 0.000, respectively. Further, the Mann-Whitney test showed mean differences between groups, with p=0.084 in the knowledge and p=1.000 in the self-efficacy variable. Conclusion: Significant changes in knowledge and self-efficacy before and after the course sessions were observed in the BL and BLFC groups. However, findings yielded insignificant differences in the mean and median between groups.